SUSTAINABLE COFFE: the importance of biological control in the preservation of coffe growing ecosystems - de Souza, Andrieli; Furlanetti, Alessandra (Revista Interface Tecnológica, 2025)
Biological control is a highly efficient method for managing agricultural pests and disease-carrying insects. This process is based on the use of its natural enemies, which can be other insects, predators, parasitoids and microorganisms. In Brazil, which ranks as the fourth largest grain producer in the world, with emphasis on coffee, biological control has proven to be a fundamental tool for the success of agriculture. The advantages of controlling harmful pests using natural resources bring many benefits to the producer and to human health, as it reduces the use of chemical insecticides, as their exacerbated use has begun to generate contamination and serious consequences for crops. To start using this control, it is necessary to identify the pest that is starting in the crop and then have knowledge of what its natural enemy is and then start acting punctually in the affected areas.